African youth on the information highway : participation and leadership in community development - Ogbu, Michael Osita; Mihyo, Paschal B. (International Development Research Centre, 2000)
As is happening in the industrialized North, the information revolution could well transform the developing nations of the South. In fact, it is already happening. Countries that only a decade ago seemed remote now have the potential to be active players in the processes of global development. As these information and communication technologies (ICTs) emerge in Africa, they offer hope to the continent's youth. This book describes a new initiative to promote the involvement of youth in Africa's new information economy. It reviews existing infrastructure, the policy environment and its impact, a.